2015
DOI: 10.1165/rcmb.2014-0331oc
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Radiation-Induced Pulmonary Fibrosis by Peripheral Targeting of Cannabinoid Receptor-1

Abstract: Radiation-induced pulmonary fibrosis (RIF) is a severe complication of thoracic radiotherapy that limits its dose, intensity, and duration. The contribution of the endocannabinoid signaling system in pulmonary fibrogenesis is not known. Using a wellestablished mouse model of RIF, we assessed the involvement of cannabinoid receptor-1 (CB 1 ) in the onset and progression of pulmonary fibrosis. Female C57BL/6 mice and CB 1 knockout mice generated on C57BL/6 background received 20 Gy (2 Gy/min) single-dose thoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
1
28
1
Order By: Relevance
“…Pharmacological inhibition or genetic deletion of Cnr1 was reported to mitigate PF and improve survival in mice following thoracic irradiation (26), but a similar role of CB 1 R in IPF and BL-PF has not yet been investigated. On the other hand, the involvement of iNOS in human IPF and in BL-PF was suggested in several prior studies (11,15).…”
Section: Cellular Localization Of Cb 1 R In Bl-pfmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological inhibition or genetic deletion of Cnr1 was reported to mitigate PF and improve survival in mice following thoracic irradiation (26), but a similar role of CB 1 R in IPF and BL-PF has not yet been investigated. On the other hand, the involvement of iNOS in human IPF and in BL-PF was suggested in several prior studies (11,15).…”
Section: Cellular Localization Of Cb 1 R In Bl-pfmentioning
confidence: 99%
“…In contrast, rimonabant at concentrations of up to 10 μM did not inhibit iNOS activity in the same in vitro assay (Supplemental Figure 4B). The peripherally restricted CB 1 R antagonist AM6545 was pharmacologically characterized earlier (32), and its antifibrotic efficacy was recently shown on prevention of radiation-induced PF (26). We next compared the antifibrotic efficacy of MRI-1867, rimonabant, and AM6546 by chronic administration of a 10 mg/kg daily oral dose for rimonabant and MRI-1867 or intraperitoneal dose for AM6545 to mice with bleomycin-induced fibrosis.…”
Section: (E) Endocannabinoid Levels In Balf (F) and Lung (G) Gene Ementioning
confidence: 99%
See 1 more Smart Citation
“…Both synthetic cannabinoids and delta-9 tetrahydrocannabinol act on the endocannabinoid receptors, the cannabinoid (CB) receptor-1 that is found in the central nervous system and CB-2 receptors in the immune system [ 13 , 14 ]. A study by Bronova et al showed CB-1 receptor-mediated signalling of pulmonary fibrogenesis in radiation-exposed mice [ 16 ]. Transient receptor potential vanilloid 4 (TRPV-4) that can be activated by endogenous N-acylamine cannabinoids and fatty acid-derived products related to anandamide during lung injury (chlorine gas or intratracheal hydrochloric acid).…”
Section: Discussionmentioning
confidence: 99%
“…Endocannabinoids are shown to promote the progression of fibrosis in liver [122][123][124], kidney [125,126], heart [127], and skin [128]. Studies in mice suggest that CB 1 receptors are associated with radiation-induced pulmonary fibrosis [129]. Cinar et al performed a detailed study in order to identify the contribution of CB 1 receptors in lung fibrosis, and have shown that both the genetic deletion of CB 1 receptors or their pharmacological inhibition with a CB 1 antagonist can attenuate lung inflammation and fibrosis, and hence increase animal survival in a mouse model of radiation-induced pulmonary fibrosis [130].…”
Section: Targeting the Endocannabinoid System For The Treatment Of Aimentioning
confidence: 99%